Management of the patient with a wearable cardiac defibrillator in a virtual remote monitoring clinic. (2nd July 2022) - Zanni, A; Sticozzi, C; Comastri, G; Rossi, L; Biagi, A; Bolognesi, M G; Piepoli, M F; Aschieri, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: the risk of sudden cardiac death (SCD) currently represents a severe problem that significantly involves the population. The implantable cardiac defibrillator (ICD) has been used to prevent SCD among patients with a high risk for life-threatening sustained ventricular arrhythmias. However, there are a number of patients at risk for SCD either awaiting a work-up for reversible causes of SCD or with acute contraindications to ICD implantation. Nevertheless, ICD implantation is dependent on defining ventricular substrate, evaluating the future risk of SCD and estimation of the patient's overall survival. The wearable cardiac defibrillator (WCD) provides an option for protection during this vulnerable period when the risk of SCD is unclear. Methods: our virtual device control clinic is managed by 3 cardiovascular technicians and 3 electrophysiologists. From August 2017 to January 2022, we included 29 patients who received WCD, 6 women (21%), with an average age of 66 years. The indications for the use of WCD were: ischemic cardiomyopathy (62, 1%) and non-ischemic cardiomyopathy (17, 24%), during cardiovascular rehabilitation pending eventual recovery of the ejection fraction (EF), waiting for genetic test result (10, 34%) or ICD explant for infection awaiting reimplantation (10, 34%).The patient is trained by technician staff to ensure the correct wearing of the WCD, the management of any alarms, the management of the device in case of arrhythmia and shock, as well as the daily replacement of the battery and the management of the remote monitoring system. Results: in virtual control device clinic Cardiovascular Technician checks the transmissions from the WCD site: only clinical parameters such as recorded ECGs (manual, asystolic, events detected but not treated and events treated with shock) and patient compliance (wearing hours per day) can be verified.The average wearing duration has been 37 days, with a daily average of 23.1 hours. We received and controlled a total of 1097 transmissions, of which 22 with events, of which 7 were generated for VT, 4 for TSV, 10 for T wave oversensing and 1 for inappropriate Shock; in all these cases, the patient has been contacted by the clinic staff for clinical management. At the end of wearing period, technical staff schedules a check-up with echocardiogram monitoring the EF to evaluate the patient's clinical path. Following the clinical evaluation, a recovery of cardiac function has been possible for 13 patients, without any implantation of ICD, whereas 16 patients underwent a defined implantation of ICD. Conclusions: the WCD has been shown to be an effective device in protecting SCD from VT/VF. Despite the small number of patients, it was necessary to take them in charge at the virtual remote monitoring clinic for proper clinical management, which generated a workload increase. Therefore, it will be important to propose a recognition of the service and its reimbursement.